Spontaneous testicular atrophy occurs despite normal spermatogonial proliferation in a Tp53 knockout rat. (22nd August 2017) - Dai, M. S.; Hall, S. J.; Vantangoli Policelli, M. M.; Boekelheide, K.; Spade, D. J.
Summary: The tumor suppressor protein p53 (TP53) has many functions in cell cycle regulation, apoptosis, and DNA damage repair and is also involved in spermatogenesis in the mouse. To evaluate the role of p53 in spermatogenesis in the rat, we characterized testis biology in adult males of a novel p53 knockout rat (SD‐ Tp53 tm1sage ). p53 knockout rats exhibited variable levels of testicular atrophy, including significantly decreased testis weights, atrophic seminiferous tubules, decreased seminiferous tubule diameter, and elevated spermatocyte TUNEL labeling rates, indicating a dysfunction in spermatogenesis. Phosphorylated histone H2AX protein levels and distribution were similar in the non‐atrophic seminiferous tubules of both genotypes, showing evidence of pre‐synaptic DNA double‐strand breaks in leptotene and zygotene spermatocytes, preceding cell death in p53 knockout rat testes. Quantification of the spermatogonial stem cell (SSC) proliferation rate with bromodeoxyuridine (BrdU) labeling, in addition to staining with the undifferentiated type A spermatogonial marker GDNF family receptor alpha‐1 (GFRA1), indicated that the undifferentiated spermatogonial population was normal in p53 knockout rats. Following exposure to 0.5 or 5 Gy X‐ray, p53 knockout rats exhibited no germ cell apoptotic response beyond their unirradiated phenotype, while germ cell death in wild‐type rat testes was elevated to a level similar to the unexposed p53 knockout rats. This study indicates that seminiferous tubule atrophy occurs following spontaneous, elevated levels of spermatocyte death in the p53 knockout rat. This phenomenon is variable across individual rats. These results indicate a critical role for p53 in rat germ cell survival and spermatogenesis.